Labor induction information leaflets—Do women receive evidence-based information about the benefits and harms of labor induction? - von Dadelszen, Peter; Tohill, Susan; Wade, Julie; Hutcheon, Jennifer A.; Scott, Janet; Green, Marcus; Thornton, James G.; Magee, Laura A.; , the WILL Pilot Trial Study Group (Frontiers in Global Women's Health, 2022)
Objectives To determine the extent to which a sample of NHS labor induction leaflets reflects evidence on labor induction. Setting Audit of labor induction patient information leaflets—local from WILL trial (When to Induce Labor to Limit risk in pregnancy hypertension) internal pilot sites or national-level available online. Methods Descriptive analysis [n = 21 leaflets, 19 (one shared) in 20 WILL internal pilot sites and 2 NHS online] according to NHS “Protocol on the Production of Patient Information” criteria: general information (including indications), why and how induction is offered (including success and alternatives), and potential benefits and harms. Results All leaflets described an induction indication. Most leaflets (n = 18) mentioned induction location and 16 the potential for delays due to delivery suite workloads and competing clinical priorities. While 19 leaflets discussed membrane sweeping (17 as an induction alternative), only 4 leaflets mentioned balloon catheter as another mechanical method. Induction success (onset of active labor) was presented by a minority of leaflets (n = 7, 33%), as “frequent” or in the “majority”, with “rare” or “occasional” failures. Benefits, harms and outcomes following induction were not compared with expectant care, but rather with spontaneous labor, such as for pain (n = 14, with nine stating more pain with induction). Potential benefits of induction were seldom described [n = 7; including avoiding stillbirth (n = 4)], but deemed to be likely. No leaflet stated vaginal birth was more likely following induction, but most stated Cesarean was not increased (n = 12); one leaflet stated that Cesarean risks were increased following induction. Women's satisfaction was rarely presented (n = 2). Conclusion Information provided to pregnant women regarding labor induction could be improved to better reflect women's choice between induction and expectant care, and the evidence upon which treatment recommendations are based. A multiple stakeholder-involved and evidence-informed process to update guidance is required.